2012
DOI: 10.3390/ijms13079014
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Berberis vulgaris L. Extract/β Cyclodextrin on Carbon Tetrachloride–Induced Acute Toxicity in Mice

Abstract: The present study investigated the capacity of formulated Berberis vulgaris extract/β-cyclodextrin to protect liver against CCl4-induced hepatotoxicity in mice. Formulated and non-formulated extracts were given orally (50 mg/kg/day) to mice for 7 days and were then intra-peritoneally injected with 1.0 mL/kg CCl4 on the 8th day. After 24 h of CCl4 administration, an increase in the levels of apartate-amino-transferase (AST), alanine-amino-transferase (ALT) and malondialdehyde (MDA) was found and a significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Consequently, hepatocyte vacuolization could be due to lipid accumulation that was detected ultrastructurally as large lipid droplets buildup in these cells. Several studies have reported hepatic centrilobular steatosis and necrosis after exposure to CCl 4 [21,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, hepatocyte vacuolization could be due to lipid accumulation that was detected ultrastructurally as large lipid droplets buildup in these cells. Several studies have reported hepatic centrilobular steatosis and necrosis after exposure to CCl 4 [21,57].…”
Section: Discussionmentioning
confidence: 99%
“…was chosen according to previous experiments with different seed oils [8,9,20], as well as the toxicant (CCl 4 ) dose of 1.0 ml/kg b.w. in 50% olive oil [21].…”
Section: Animal Treatmentmentioning
confidence: 99%
“…The B. vulgaris-aqueous extract doses were chosen according to previous studies on the plant or on its main constituent (berberine), and on the basis of acute toxicity study of the plant [11][12] . After 42 days, the animals were given rest overnight, and then on the next day they were sacrificed by cervical dislocation under light ether anesthesia.…”
Section: Experimental Procedurementioning
confidence: 99%
“…(Del Valle 2004). It was confirmed that hepatoprotective effects of some compounds have been increased when they formulated with CD, because CD could improve the performance of compounds in terms of efficacy, solubility, and bioavailability (Hermenean et al 2012). According to effect of CD on TMX sustained release, for the first time we decided to simply evaluate about the protective effect of CD on hepatotoxicity of TMX.…”
Section: Discussionmentioning
confidence: 96%